Emphasising the Problem or the Solution in Charitable Fundraising for International Development. Issue 6 (3rd June 2018) - Clark, Jeremy; Garces-Ozanne, Arlene; Knowles, Stephen
Abstract: We conduct a laboratory experiment to test the effect on charitable donations to international development NGOs (INGOs) of emphasising current deprivation in a developing country, versus emphasising the potential good a donation can achieve. Using a double-blind dictator experiment with earned endowments, we find that varying the information/emphasis has no significant effect on total donations, nor on the probability of donating. We find suggestive evidence that an emphasis on current deprivation may raise the variance of donations, and thus the size of donations conditional on donating, but the effect is not significant in hurdle models that explicitly recognise this.